Os efeitos no início da convergência contábil da IFRS 9 para as instituições financeiras do Sistema Financeiro Nacional (COSIF) - Lacanna, Ana Paula Correia (2018)
The process of implementing international accounting standards, IFRS (International Financial Reporting Standards) was adopted internationally by financial institutions, in order to allow its financial statements to be more transparent and comparable with other financial reports issued by other companies thus enabling the main users of Accounting to understand in a harmonious and universal language the accounting numbers and their explanatory notes, thus assisting them in the process of decision-making in the accounting, management, economic and operational spheres. In Brazil, since 2010, financial institutions have started to prepare and disclose their consolidated financial statements in two different standards, the first standard being called BRGAAP, through the use of standards and procedures issued by the Central Bank of Brazil (BACEN) and the second standard, denominated IFRS, through the issuance of standards issued by the IASB, converged and translated by the Accounting Pronouncements Committee (CPC) and endorsed by BACEN through Resolutions. From the beginning of the process of convergence to international standards, the IASB standard that most impacted the Bank's reality was IAS 39 Financial Instruments. IAS 39 has always been considered complex since it was issued. After the 2008 crisis, it was possible to carry out a review of the standard by the regulatory agencies, resulting in the institutionalization of a project that segmented this work into three main stages, the first phase being the classification and measurement of financial instruments, second stage on the introduction of a new model of calculation of loss incurred and the third step on the accounting of hedge accounting, resulting in the publication of IFRS 9 on July 24, 2014, with a mandatory date as of January 1, 2018. The purpose of this study is to explore the differences in the criteria for classification and measurement of financial instruments, impairment and accounting for hedge accounting, as set forth in IAS 39 (International Accounting Standard) and IFRS 9. Related to this, as a data source, the report containing the quarterly financial information of the Brazilian Financial Institutions was selected on the BACEN website and selected the ranking of the 10 largest Financial Conglomerates in Brazil, whose search filter corresponded to the "Total Assets" field, as of March 31, 2018 , obtaining a representativity of 87% of the total. The target of this study is to evaluate the main effects of the adoption of IFRS 9 in the Financial Statements of Financial Institutions for the Institutions they adopted before 2018 and the impact estimates for those that will adopt the standard in 2018. Differences in accounting criteria IAS 39 and IFRS 9 were evaluated under the premise that the classification and measurement of financial assets and especially the new model in the calculation of the impairment will have a significant impact on the financial statements of the Financial Institutions. For the empirical test, the study was based on the review of the Complete Financial Statements in IFRS, on the base dates December, 31, 2017 and March, 31, 2018, in order to verify the actual / estimated impacts to the Institutions. As a conclusion, the analyzes showed that there were changes in the classification and measurement of financial assets, as well as the new calculation of the impairment impacted / would significantly impact the Shareholders' Equity, through the increase with the impairment expense, as was initially expected. Regarding the criteria for re-accounting of hedge accounting, there were no changes, as the banks chose to remain in accordance with IAS 39 criteria, since the stage of IFRS 9 regarding hedge accounting was not fully completed